In-Situ Stresses In Rock Masses: A General Review - Bambang Widarsono (Scientific Contributions Oil and Gas, 2000)
The in situ state of stress is a rock's point-to-point property that must be taken into consideration in every subsurface engineering activity This has been realized to an increasing extent over the past 10 - 20 years. Good quality in situ stress information enhances the quality of engineering designs such ax for mining, petroleum and geothermal production. In turn good engineering designs will support the process of decision making in related industries. However, efforts are required to encourage the use and integration of this information into the engineering activities.This paper is basically a general review over the in situ stress that encompasses various aspects, among others are concept, causes/sources that generate it, influencing factors, the effect of scales, techniques for measuring it, and its distribution throughout the lithosphere. The review is supported by works and conclusions that have been made by various investigators in the past. The relative absence of the use of in situ stress information in petroleum engineering practices in Indonesia is also discussed. This includes the absence of demand upon the information, probable consequence, and the field cases that are likely caused by the absence.Apart from the importance of in situ stress information shown by the review, it has also prompted the need to apply proper use of in situ stress information in relation to the corresponding engineering scales. Inappropriate measurement techniques assigned to an engineering problem, which corresponds to a certain scale, will certainly lead to a serious misprediction over the expected outcome. These all are hoped to provide operators in the industry a complete general view over the in situ stresses their importance.